ANALISIS PENGARUH LOAN LOSS PROVISION, BOARD SIZE, EQUITY TO ASSET RATIO, INDEKS LERNER TERHADAP PRICE/EARNING TO GROWTH RATIO, DENGAN MENGGUNAKAN RETURN ON ASSET SEBAGAI VARIABEL INTERVENING (Studi Kasus pada Bank Umum di Indonesia pada tahun 2010-2015) - Prasetyo, Ivan; Mawardi, Wisnu (Diponegoro Journal of Management, 2018)
Value and growth of a company can be measured by PEG (Price/Earning to Growth Ratio), this ratio compare PER (Price/Earning Ratio) with Annual EPS Growth. Value and growth of banking is very important because banking is the backbone of a country's economy and plays an important role to support economic growth, increase equity through national development, as well as improving the welfare of people in that country. Therefore, this study takes Analysis of Loan Loss Provision, Board Size, Equity to Asset Ratio, Lerner Index to Price / Earning to Growth Ratio, using Return on Asset as Intervening Variable (Case Study at Commercial Bank in Indonesia on year 2010-2015) as the title. The sample of this research is 20 commercial banks spread throughout Indonesia, with 5 years period (2010-2015), therefore obtained 100 data in this research. The data was obtained through the Annual Report of Commercial Banks in that period as well as directly quoting financial data from Bloomberg. Data analysis using Multiple Linear Regression Analysis and previously tested using classical assumption test.The result of this research indicate that LLP have negative significant effect to ROA, Board Size and EAR negative but none significant effect to ROA, while LI has positive significant effect to ROA. While the research on PEG shows that Board Size and EAR have negative, but none significant effect on PEG. LLP shows negative significant effect on PEG. While ROA and LI has positive but none significant effect to PEG. ROA can’t be a intervening variable that represent independent variable in this research to dependent variable